2002
DOI: 10.2337/diacare.25.8.1398
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Pharmacodynamics, Safety, and Tolerability of a Single-Dose of NN2211, a Long-Acting Glucagon-Like Peptide 1 Derivative, in Healthy Male Subjects

Abstract: OBJECTIVE—The primary objective of the present study was to investigate the safety, tolerability, and pharmacokinetics of a single dose of NN2211, a long-acting glucagon-like peptide 1 (GLP-1) derivative, in healthy male subjects. The secondary objective was to investigate the pharmacodynamics of NN2211. RESEARCH DESIGN AND METHODS—In a double-blind, randomized dose, escalation, placebo-controlled study, healthy male subjects were enrolled at eight consecutive dose levels (1.25, 2.5, 5.0, 10.0, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
224
1
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(243 citation statements)
references
References 30 publications
15
224
1
3
Order By: Relevance
“…The half-life after intravenous or subcutaneous administration in humans has been reported to be ∼5 min [19]. Liraglutide has been reported to show an elimination half-life of 8.1 h [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The half-life after intravenous or subcutaneous administration in humans has been reported to be ∼5 min [19]. Liraglutide has been reported to show an elimination half-life of 8.1 h [19].…”
Section: Discussionmentioning
confidence: 99%
“…The half-life after intravenous or subcutaneous administration in humans has been reported to be ∼5 min [19]. Liraglutide has been reported to show an elimination half-life of 8.1 h [19]. This increase in the halflife of liraglutide is most likely to be mediated via a lower susceptibility to metabolism by DPP-IV [20] and a high degree of albumin binding of liraglutide (as has been shown for other fatty acid derivatives [21,22]); moreover, after subcutaneous administration, an additional prolongation of the half-life is mediated by slow absorption of liraglutide from the injection site, as evidenced by the further increase in half-life observed with subcutaneous vs intravenous administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the delivery of GLP-1 by injection is hampered by the rapid degradation and clearance of the peptide (14). Moreover, cramping and nausea are common side effects of GLP-1 mimetics and limit the injected doses that are tolerable (15,16). The doses used to promote ␤ cell growth in rodents, typically 50-100 g͞kg of body weight (10,13), are significantly higher than the Ͻ2 g͞kg of body weight dose that is tolerable in humans (17) and greatly exceed the dose of the GLP-1 mimetic exenatide (Byetta) that is currently prescribed to treat type 2 diabetes patients (5 g injected twice daily).…”
mentioning
confidence: 99%
“…[15][16][17] Liraglutide and CJC-1131 are two GLP-1 analogs with chemical modifications, that can bind noncovalently or covalently to HSA in vivo and exhibited a half-life of more than 10 h above after administration. 18) In addition, Lee et al studied the in vitro and in vivo activity of a PEGylated GLP-1 analog, and the results indicated that it had the bioactivity of native GLP-1, and that its in vivo half-life was significantly prolonged. 12) However, to date, studies of the expression and purification of GLP-1 fusion protein with similar bioactivity have been few.…”
mentioning
confidence: 99%